Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Using $$\ln(x) = \int_1^x \frac{1}{t} dt$$

Show that for $x > 0$, $\ln\left(\frac{1}{x}\right) = -\ln(x)$

I am following a provided answer and didn't quite understand the following transformation and why/how it is done:

$$\ln\left(\frac{1}{x}\right) = \int_1^{\frac{1}{x}} \frac{1}{t}dt$$

$$~u = \frac{1}{t}, du = \frac{-1}{t^2}dt$$

$$= -\int_1^{\frac{1}{x}} t\frac{dt}{t^2}$$

$$=-\int_1^x \frac{1}{u}du$$

$$= -\ln(x)$$

I don't understand how the limits of integration were changed in the $2nd$ and $3rd$ term (from $\frac{1}{x}$ to $x$). Is there a property that makes this correct or is there some other reasoning behind the change?

share|cite|improve this question
$\qquad t=1\iff u=1;\quad t=1/x\iff u=x$ – anon Jun 13 '12 at 6:50
up vote 2 down vote accepted

\begin{align} \ln\left(\frac{1}{x}\right) & = \int_1^{\frac{1}{x}} \frac{1}{t}dt & & {\text{Replace $x$ by $\dfrac1x$ in the definition}}\\ u & = \frac{1}{t} & &{\text{This is the substitution you are making}}\\ du & = \frac{-1}{t^2}dt & &{\text{This is because }\dfrac{du}{dt} = - \dfrac1{t^2}}\\ \ln\left(\frac{1}{x}\right) & = \int_1^{\frac{1}{x}} \frac{1}{t}dt & = \int_1^{\frac{1}{x}} -t \times \left(-\frac{1}{t^2}dt \right) & \text{Multiply and divide the integrand by $-t$} \end{align} In the above integrand, we can replace $-\dfrac{1}{t^2}dt$ by $du$ and $-t$ by $- \dfrac1u$.

Note that we are making the change of variable, the integrand is in terms of $u$ now.

Hence, we need to look at the limits for the variable $u$ in the integral.

We have the transformation that $u = \dfrac1t$. Hence, if $t$ goes from $1$ to $1/x$, then $u$ goes from $1$ to $x$. This is because when $t=1$, $u = \dfrac11 = 1$. Similarly, if $t = 1/x$, then $u = \dfrac1{1/x} = x$.

(For example, if $t$ goes from $1$ to $2$, then $1/t$ goes from $1$ to $1/2$.)

Hence, we get that \begin{align} \ln \left( \dfrac1x\right) & = \int_1^{\frac{1}{x}} -t \times \left(-\frac{1}{t^2}dt \right) & = \int_1^x \left(-\dfrac1u \right) \times du = - \int_1^x \dfrac{du}{u} = - \ln(x) \end{align} where the last equality is obtained since we have defined $\ln(x)$ as $\displaystyle \int_1^x \dfrac{dt}{t}$.

share|cite|improve this answer

I like to add that this change of integral limts is due specifically to the terminals as follows: If $g$ is a function continuously differentiable on $[a,b]$ and $f$ continuous on $J=g ([a, b​​])$, let $F$ is a primitive of $f$ on $J$ then: $$\forall t \in [a,b] \quad (F \circ g)'(t)=F'(g(t)) g'(t) = f(g(t)) g'(t)$$ Then : $$\begin{align*}\int_a^b f(g(t)) g'(t) dt &= \int_a^b (F \circ g)'(t) dt \\ &=\left[(F \circ g) (t)\right]_a^b \\ &= F(g(b))-F(g(a)) \\ &= [F(t)]_{g(a)}^{g(b)} \\ &= \int_{g(a)}^{g(b)} f(t) dt \end{align*}$$ Now try to compare this with the special case above.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.